Psammomatous Melanotic Schwannoma: A Challenging Histological Diagnosis - Rastine Merat; Ildiko Szalay-Quinodoz; Emmanuel Laffitte; Gürkan Kaya (MDPI AG, 2015)
Psammomatous melanotic schwannoma (PMS) is a rare pigmented tumor that can be part of the Carney complex. Here, we describe the case of a 35-year-old female patient presenting an isolated subcutaneous PMS. Histopathological analysis could not formally exclude the malignant nature of the tumor. The challenging histological diagnosis and consequently the management of the patient are described.